Fundamental Aspects of Superdisintegrants: A Concise Review - Gannu Praveen Kumar (Journal of Global Pharma Technology, 2012)
Disintegrants are substances or mixture of substances added to the drug formulation that facilitates the breakup or disintegration of tablet or capsule content into smaller particles that dissolve more rapidly than in the absence of disintegrants. An oral solid dosage form should deally disperse into the primary particles from which it is prepared. The inclusion of the right disintegrant is a prerequisite to get optimal bioavailability in tablets and capsules which need rapid disintegration. Superdisintegrants are used to improve the efficacy of solid dosage forms. This is achieved by decreasing the disintegration time which in turn enhances the drug dissolution rate. Superdisintegrants are generally used at a low level in the solid dosage form, typically 1-10 % by weight relative to the total weight of the dosage unit. Examples of Superdisintegrants are crosscarmelose, crospovidone, sodium starch glycolate which represent example of a crosslinked cellulose, crosslinked polymer and a crosslinked starch respectively. This review comprises various kinds of superdisintegrants, which are being used in the formulation to provide safe and effective drug delivery with patient's compliance. Keywords: Disintegrants, Tablets, Superdisintegrants.